Penentuan Kondisi Optimum Penyerapan Anion Kromat Pada Silika Termodifikasi Dimetilamina - Vivi Chaniasi; Budhi Oktavia; Indang Dewata; Ananda Putra (Jurnal Periodic Jurusan Kimia UNP, 2022)
Heavy metal is the most dangerous was for the ecosystem because is not biodegradable, toxic, and carcinogenic even in a low concentration (ppm). It usually experienced some conditions such as not dissolved, precipitated, fused, absorbed, anorganic, reducer, oxidize, and free metal. One of the heavy metals that can cause negative effects for human and other living creature is Kromium Ion. The waste of the usage of Krom can damage the environment.  Krom is a heavy metal that has dangerous affects that we have to be aware of. Krom (VI) on water was found 2 form od specieses, as an anion (Cr2O7)2- (In Acid solution) and anion (CrO4)2- (In Alkaline solution). One of the ways how to overcome Krom in a waste is by absorb it with an adsorbent, modified Silica DMA. It characterized with an electron microscope scanning, infrared spectrum, K2CrO4 adsorption from liquid solution which investigated in some pH level, contact time, K2CrO4 first concentration. The result of the experiment shows that modifying silica with DMA increases the adsorption capacity for Kromat. Langmuir Isotherm Adsorption resulting regression coefficient on Silica R2=0,8488, and for the modified Silica R2=0,9054. Kromat maximum adsorption capacity on 1,255 mg/g Silica and 2,26 mg/g modified Silica with first concentration of K2CrO4 100 mg/L can be reach on pH 2 with 90 minutes mixing process.